2012
DOI: 10.1530/eje-11-1051
|View full text |Cite
|
Sign up to set email alerts
|

Comparison of serum testosterone and estradiol measurements in 3174 European men using platform immunoassay and mass spectrometry; relevance for the diagnostics in aging men

Abstract: Background: The limitations of serum testosterone and estradiol (E 2 ) measurements using nonextraction platform immunoassays (IAs) are widely recognized. Switching to more specific mass spectrometry (MS)-based methods has been advocated, but directly comparative data on the two methods are scarce. Methods: We compared serum testosterone and E 2 measurements in a large sample of middle-aged/elderly men using a common platform IA and a gas chromatography (GC)-MS method, in order to assess their limitations and … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

4
120
1
2

Year Published

2014
2014
2021
2021

Publication Types

Select...
6
4

Relationship

2
8

Authors

Journals

citations
Cited by 176 publications
(127 citation statements)
references
References 33 publications
4
120
1
2
Order By: Relevance
“…Furthermore, serum DHT was rarely measured in population-based studies as few in-house DHT immunoassays were available and none in multiplex or valid single-tube formats (23). Similarly, serum E 2 was usually measured by direct immunoassays, which are inaccurate at the low circulating E 2 levels prevailing in men of all ages (24,25,26). Finally, few studies reported measuring serum testosterone, DHT, and E 2 in studies of thousands of participants (21,22).…”
Section: Discussionmentioning
confidence: 99%
“…Furthermore, serum DHT was rarely measured in population-based studies as few in-house DHT immunoassays were available and none in multiplex or valid single-tube formats (23). Similarly, serum E 2 was usually measured by direct immunoassays, which are inaccurate at the low circulating E 2 levels prevailing in men of all ages (24,25,26). Finally, few studies reported measuring serum testosterone, DHT, and E 2 in studies of thousands of participants (21,22).…”
Section: Discussionmentioning
confidence: 99%
“…A good quality immunoassay was used for testosterone measurements; therefore, the hormone data can be considered reliable, although mass spectrometry was not used (28,29). Only total testosterone was measured, because sex hormone-binding globulin (SHBG) levels were not available.…”
Section: Potential Study Limitationsmentioning
confidence: 99%
“…The analytical sensitivity of the assays was 0.5 nmol/l for TT, 55 pmol/l for E 2 , 0.1 mIU/ml for FSH, 0.05 mIU/ml for LH, and 0.02 nmol/l for SHBG. TT measurement by immunoassay has been validated by isotopic dilution-liquid chromatography-tandem mass spectrometry method for values higher than nanomolar (12). Calculated free testosterone (cFT) was calculated as demonstrated previously (13).…”
Section: Biochemical and Anthropometric Measurementsmentioning
confidence: 99%